(untitled) (Asian Journal of Social Science Studies, 2022)
Most of previous studies on metaphor and metonymy at home and abroad are limited to the verbal mode, ignoring non-verbal mode. A few studies on multimodality mainly focus on the basic role of metonymy, lacking adequate attention to the representation of multimodal metaphor and metonymy, and the role in constructing specific images from the perspective of social pragmatic function. This paper takes the cover cartoons of the Economist as data to analyze the recognition and representation of multimodal metaphors and metonymy. Then, from the perspective of social pragmatics, we quantitatively analyze the symbolic signs of the source domain of the covers in the past decade, and reveal their roles in constructing the image of China. This research is to understand the linguistic approach of “how to reconstruct China’s image” and “how to construct” by international media, which can provide implication for Chinese dissemination and diplomatic strategy in the digital age.